Effect of di-calcium phosphate on calcium balance and body condition score of dairy cows fed Napier grass (Bangladesh Journal of Animal Science, 2014)
A research work was undertaken to evaluate the feeding effects of di-calcium phosphate (DCP) on calcium balance and body condition score of dairy cows fed Napier grass. The trial was conducted in the village Alokdiar of Shajadpur upazilla under Sirajgonj district. Twenty crossbred lactating dairy cows of 320 ±15.5 kg live weight were used for the trial. Animals were equally and randomly allocated into four groups, T0 (Napier+concentrate), T1 (Napier+concentrate+100g DCP), T2 (Napier+concentrate+150g DCP) and T3 (Napier+concentrate+200g DCP). Total DMI did not differ significantly (p>0.05) among the groups but highly significant differences (p